The assignments and functions of the Financial Service Authority in disputes related to the Legal Protection for the Consumers in Indonesia - Ahmad, Sufmi Dasco; Pujiyono, Pujiyono (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
This article aims to describe and examine the problems of how the Financial Services Authority’s assignments and functions in disputes related to legal protection for consumers. This research is a normative legal research that is prescriptive. Secondary data types include primary and secondary legal materials.The primary datas is collected from many regulations about financial, financial service authority, consummen and banking. Data collection techniques used are library studies and cyber media, and the analytical techniques are deductive by syllogism methods. The research result shows that the Financial Services Authority in carrying out its duties and functions of consumers protection was carried out with three forms of action, namely, loss prevention measures, consumers complaints services, and legal defense actions. The three tasks and functions must be carried out maximally by applying the basic principles of the implementation of the OJK’s duties so that it can accommodate the protection of consumers and society.